Visualization of blood vessels by corrosion technique - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2017)
Corrosion technique is one of the basic and widely used methods of visualization of vascularization of organs in the anatomy of humans and animals. It consists in filling vascular (blood or lymph), wires or cavernous organs material, e.g., injection. Mass based on wax or putty material based on rubber, synthetic resin and subsequently etching the soft tissues. Ultimately obtained castings of these structures. The aim of the study was to evaluate the usefulness of this technique in morphological studies. In retrospect, corrosion technique has been used already in the seventeenth century, however, because of the use of filler materials such as water, liquid dyes, and even air, obtained anatomical specimens were unstable, therefore, did not yield the desired effect of the test. With time, however, the corrosion technician went through some modifications and new solutions in the embodiment and above all in the chemical composition of the filling material. In the twentieth century, they began to use compounds such as polyester resins, methyl methacrylate or polyvinyl chloride, the specific properties of these compounds allowed the visualization and consolidation of fine anatomic structures in the vascular system, the bronchial tree or the bile ducts. Extensive use of this technique in medicine, veterinary and comparative anatomy of vertebrates underlines its usefulness and the need to use.